ACTIVITIES OF LOCAL AUTHORITIES UNDER THE CONDITIONS OF MARTIAL LAW - Tsymbaliuk, Valerii (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2023)
Aim: to analyze the specifics of the activities of local authorities under the conditions of martial law. In this regard, the following tasks are implemented in the presented material: 1) the peculiarities of the legal status of local authorities under conditions of martial law are determined; 2) the content of the powers of local authorities under the conditions of martial law as the basis of their practical activities is revealed. Research methods: general theoretical and analytical in combination with systemic and complex approaches. Results: it is shown that a dualistic model of local power, represented by local state administrations and local self-government and implemented in the Ukrainian state-building practice. The author determined that the critical specificity of the conditions of martial law emphasizes defense and security issues, which prompted the legislator to foresee the possibility of the formation of military administrations that take over the functions of local authorities. Discussion: an analysis of the norms regulating the activities of local authorities under the conditions of martial law gives grounds for asserting that the legislator tried to write out the powers of military administrations rather carefully. The actual activity of the specified power institutions consists in 1) introduction and implementation of measures of the legal regime of martial law; 2) ensuring the effective usage of all available resources to support the functioning of the relevant territories; 3) managing critical infrastructure and housing and communal services despite of existing and potential military threats; 4) managing the humanitarian sphere; 5) implementing of effective public administration taking into account the peculiarities of the legal regime of martial law.